2010
DOI: 10.1111/j.1747-0765.2010.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of vivianite formed on the roots of paddy rice grown in pots

Abstract: An understanding of the phosphate (P) dynamics in paddy rice fields is the basis for improving P fertilizer efficiency and reducing P loss from paddy fields. During the ripening stage of rice plants cultivated in pots, we identified vivianite on the roots. We placed 3 kg of air-dried soil in a pot with coated urea (1 g N), coated potassium sulfate (1 g K 2 O) and granular superphosphate (1 g P 2 O 5 ) as basal fertilizers. Three rice seedlings were transplanted into each pot and grown until the ripening stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…The observed morphological properties of vivianite crystals resembled those reported by Nanzyo et al (2010Nanzyo et al ( , 2013. Figure 6a shows the crystal aggregates formed on thin rice roots from the CF micro plot that were sampled on September 2 (104 DAT).…”
Section: Observation Of Vivianite Crystals On Rice Rootssupporting
confidence: 68%
See 1 more Smart Citation
“…The observed morphological properties of vivianite crystals resembled those reported by Nanzyo et al (2010Nanzyo et al ( , 2013. Figure 6a shows the crystal aggregates formed on thin rice roots from the CF micro plot that were sampled on September 2 (104 DAT).…”
Section: Observation Of Vivianite Crystals On Rice Rootssupporting
confidence: 68%
“…More recently, Nanzyo et al (2010Nanzyo et al ( , 2013 confirmed the presence of vivianite crystals on aged rice roots under reducing conditions by X-ray microdiffraction, scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) analysis. Vivianite was present as crystal aggregates both within and on the surface of aged rice roots after air-drying the samples.…”
Section: Introductionmentioning
confidence: 85%
“…Wang et al (2013) reported that amount of ROL per plant and Fe plaque increased dramatically from tillering to ear emergence stages and then decreased at the grain-filling stage. Nanzyo et al (2010) found that the quantity of root Fe plaque reached its peak at the tillering stage, after which it gradually decreased. Furthermore, dissolved organic matter (DOM) secreted by roots might influence the formation of Fe plaque since DOM could provide protons and electrons for reductive dissolution of Fe plaque (Zhang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that the ROL and Fe plaque of rice roots could change in amount and composition during growth (Nanzyo et al 2010;Wang et al 2013). Wang et al (2013) reported that amount of ROL per plant and Fe plaque increased dramatically from tillering to ear emergence stages and then decreased at the grain-filling stage.…”
Section: Introductionmentioning
confidence: 99%
“…Their finding was directly related to rice plants. Their observation was later confirmed using X-ray microdiffraction and SEM-EDX analyses on rice roots grown in pots (Nanzyo et al 2010) and in ordinary paddy fields (Nanzyo et al 2013). Figure 5.11a shows vivianite crystal aggregates formed on rice roots.…”
Section: Detection Of Vivianite In Paddy Field Soilmentioning
confidence: 72%